O design de estamparia têxtil e a educação: uma prática educativa no 9º ano do ensino fundamental na Escola Municipal de 1º Grau Chácara das Flores - Fleck, Luis Tadeu Martil (2008)
This research was part of the Research Line in Education and Arts/ PPGE/CE/UFSM, developed at the Federal University of Santa Maria/RS. The research was contextualized in the formal education, where the research-action was developed at Chácara das Flores Municipal Elementary School, in Santa Maria/RS, with ninth grade students. This research materialized, in general lines, the investigation of critical education practice by using as basis the theoretical ideas of the Printed Textile Design with ninth grade students of ntermediate school. In special, it itended: to identify and to analyse the conception and action of students related with their understanding of Printed Textile Design as a modality; to trace, in colaboration with the students, practical and educative activities with critical view, having as support the learning and perception of pedagogical knowledge-making in a critical view related with printed textile design; to analyse the knowledge of the printed textile design created by the education practice, and the educational possibilities in the learning process by the materialization of printed textile design sketches; to punctuate a critical scholastic educative practice of the printed textile design in the Elementary School. The review of theoretical ideas was based on the following researchers: FREIRE (1975), EFLAND (2005), CARDOSO (2004), DONDIS (1997), REDIG (1976), OSTROWER (1987) and LUBART (2007). The research metodology was organized from qualitative research/action-research, and the instrumental used to collect data were real observations, diary notes, semi-structured interviews with students and their parents, portfolio and documental analysis. The analysis of critical educative practice in Printed Textile Design outlined the research course with the students of the ninth grade of Chácara das Flores Municipal Elementary School. The speeches of the students and their parents propitiated meaningful activities and visual creations related to Printed Textile Design and to the students social and cultural world. By the end of this research, it was verified that the critical educative practice, based on Freire and related with Printed Textile Design, contributed to the Visual Arts teaching because that kind of practice deal with this knowledge (PTD) in a critical configuration, contextualizing and incresing the students culture through an efectively, consciousness and humanizing educative practice.